Physical framework for a counselling environment in India: Thematic analysis of counsellors' perceptions. Issue 2 (6th February 2020) - Dey, Anjali Miriam; Kumar, Aneesh
Abstract: The influence of the physical environment on the counselling process is an inevitable part of a counselling session. However, there is little insight in Indian research into the desirable elements of the physical environment of the counselling room that helps facilitate a counselling session. Interviews were conducted with 10 professional counsellors in India. Thematic analysis of the data brought out various Basic and Organising themes under the following three Global themes: (a) Elements of the physical framework; (b) Counsellor's perspectives about the physical framework in counselling; and (c) Motivation to build a framework. The findings show how counsellors can systematise the physical framework to help construct the counselling session effectively.